ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA BERDASARKAN SELF EFFICACY - Helena Belinda; Nora Susilowaty (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This study aims to determine the type of self-efficacy is the most at the level of low, medium and high ability to solve math problems and to describe the problem-solving ability of students in solving math problems in the material PLSV and PTLSV based on three dimensions of self-efficacy. This type of research is descriptive research using a qualitative approach. The subjects of this study were 9 students from grade VIIC Junior High School in Parongpong. Data collection in the form of written tests and interviews. The results showed that the most self-efficacy dimension for each mathematical ability is magnitude. At a high level of mathematical ability, most of the dimensions of self-efficacy students are able to perform each step of solving the Polya problem well. At the level of moderate mathematical ability, each dimension of self-efficacy students can partially understand the problem well and completely. At the stage of designing solutions some students have not been able to make a complete problem-solving plan and some do not make plans. At the stage of implementing the plan on each dimension of self-efficacy some students can work according to plan but not yet complete and visible from the results obtained less thorough. At the last stage of the Polya step, some students did not recheck and some did recheck. At the level of low mathematical ability, students from each dimension of self efficacy have not been able to desig n solutions and implement problem solving properly and completely according to plan, at the stage of re-examining students (dimension of self efficacy generality) re-examining their work and students (dimension of self efficacy magnitude and strength) do not re-examine their work.